2019
DOI: 10.21203/rs.2.18218/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust Statistical Stopping Criteria for Automated Screening in Systematic Reviews

Abstract: Active learning for systematic review screening promises to reduce the human effort required to identify relevant documents for a systematic review. Machines and humans work together, with humans providing training data, and the machine optimising the documents that the humans screen. This enables the identification of all relevant documents after viewing only a fraction of the total documents. However, current approaches lack robust stopping criteria, so that reviewers do not know when they have seen all… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We will use supervised machine learning (ML) to accelerate the screening process through an iterative cycle of training, testing against manual classification and re-training of the ML algorithm until a stopping rule is met ( Callaghan & Müller-Hansen, 2019 ). We will use NACSOS research platform for screening process and Python scikit-learn library for machine learning ( Callaghan et al ., 2020 ; Pedregosa et al , 2012 ).…”
Section: Literature Search Screening and Data Managementmentioning
confidence: 99%
“…We will use supervised machine learning (ML) to accelerate the screening process through an iterative cycle of training, testing against manual classification and re-training of the ML algorithm until a stopping rule is met ( Callaghan & Müller-Hansen, 2019 ). We will use NACSOS research platform for screening process and Python scikit-learn library for machine learning ( Callaghan et al ., 2020 ; Pedregosa et al , 2012 ).…”
Section: Literature Search Screening and Data Managementmentioning
confidence: 99%
“…"> Screening —Machine learning tools can help to increase efficiency in screening by prioritising relevant research so that eligible studies can be found early on in the screening process and other stages (meta‐data extraction) can begin sooner (O'Mara‐Eves et al, 2015), although traditionally, all records should be screened by at least one human (CEE, 2018). Recent methodological developments have suggested processes of transparently cutting off screening processes at given levels of confidence about the completeness of the process (Callaghan & Müller‐Hansen, 2019). In addition, named entity recognition can be used to identify terms from a predefined dictionary or taxonomy to support screening: for example, Lamb et al (2019) used a dictionary of city names to identify case studies from the climate literature. …”
Section: How Evidence Synthesis Technology Can Support Systematic Map...mentioning
confidence: 99%